Anti-adhesion hernia repair patch

By adopting a multi-layer structure design on the hernia repair patch, using absorbable medical membranes and mesh braided substrates, the problems of easy adhesion and insufficient mechanical properties of the existing hernia repair patches are solved, achieving higher safety and stability.

CN222487735UActive Publication Date: 2025-02-18SHANGHAI XINHUA RUISI MEDICAL SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202323111934.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-02-18
Estimated Expiration
2033-11-17

AI Technical Summary

Technical Problem

Existing hernia repair patches are prone to adhesions with internal organs, leading to serious complications, such as intestinal obstruction, intestinal necrosis, intestinal fistula, etc., and insufficient mechanical properties, and there is a risk of rupture, leading to recurrence of hernia.

Method used

Anti-adhesion hernia repair patch with a multi-layer structure, the surface layer is an absorbable medical membrane, made of levoligopolylactic acid polycaprolactone copolymer, the surface layer on the other side is a substrate, the substrate adopts a mesh braided structure, through The double-comb three-needle uses a satin mesh structure to form a diamond mesh structure, reducing adhesion to the viscera.

Benefits of technology

It effectively reduces the risk of adhesion to internal organs, improves anti-tension strength and abdominal wall compliance, reduces the occurrence of postoperative complications, and reduces the risk of hernia recurrence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222487735U_ABST
    Figure CN222487735U_ABST
Patent Text Reader

Abstract

The utility model discloses an anti-adhesion herniorrhaphy patch, which is characterized in that the surface layer on one side is an absorbable medical film, and the anti-adhesion herniorrhaphy patch further comprises a layer of base material. The base material is a net-shaped braided fabric and is provided with a double-bar three-needle warp satin eyelet weave structure, two guide bars transversely move left and right, yarn laying and looping are reversely and symmetrically carried out, a diamond-shaped mesh structure is formed, and the two guide bars are in a one-penetrating and one-empty mode. The anti-adhesion stent is good in tensile strength, good in abdominal wall compliance, small in foreign matter reaction, capable of promoting ingrowth of tissues and capable of effectively achieving the anti-adhesion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of medical devices, and in particular relates to the shape and structure of a hernia repair patch and a substrate, and specifically relates to an anti-adhesion hernia repair patch. Background Art

[0002] Hernia refers to the movement of organs away from their original position and into another part of the body through weak points, defects or holes in the human body. The most common site for hernia is the abdomen. When the abdominal organs or omentum move away from their original position through normal or abnormal holes or fissures in the abdominal cavity, it constitutes an intra-abdominal hernia, which cannot be seen visually, such as omental foramen hernia and diaphragmatic hernia. When the abdominal organs protrude to the surface of the body through congenital or acquired defects or weak areas of the abdominal wall, forming a mass locally, it is called an extra-abdominal hernia. Extra-abdominal hernia is much more common than intra-abdominal hernia, and can occur in all age groups from children to the elderly, and elderly men are the high-risk group for this disease. Although extra-abdominal hernia is not a fatal disease, it will cause great pain to the patient, seriously affecting the quality of life, and there may be a variety of complications, which can be life-threatening in severe cases.

[0003] The current gold standard for the treatment of extraperitoneal hernia is "tension-free herniorrhaphy", which is a surgical procedure in which a repair device with a specific shape or structure is made of material and implanted into the defect or weak area of ​​the abdominal wall. By stimulating the body to rapidly proliferate a large amount of fibrotic tissue on the repair device, the defective tissue is repaired and strengthened, ultimately achieving the goal of completely curing the hernia lesions.

[0004] It has been widely confirmed that polypropylene patches can form adhesions with the intestine when exposed to the intestinal serosa, and may cause serious complications such as intestinal obstruction, intestinal necrosis, and intestinal fistula. Patches woven from a single material cannot meet the performance requirements of the human body for patches. For example, polypropylene is prone to adhesion to internal organs, polyester has many postoperative complications, and must be removed after infection, which can easily cause hernia recurrence. Expanded polytetrafluoroethylene has poor firmness and anti-infection ability, and the patch must be removed once infected. At the same time, some current hernia repair patches have insufficient mechanical properties and there is a risk of patch rupture. Utility Model Content

[0005] In view of the above-mentioned defects in the prior art, the utility model provides an anti-adhesion hernia repair patch, which has a shape and structure formed by a specific weaving method of a base material and is applied to the patch, thereby overcoming the above-mentioned problems.

[0006] The utility model provides an anti-adhesion hernia repair patch, which is a multi-layer structure, one side of which is an absorbable medical film; it also includes a base material; the preparation material of the absorbable medical film is selected from L-polylactic acid-polycaprolactone copolymer.

[0007] In some specific embodiments, the anti-adhesion hernia repair patch is a two-layer structure, with one surface layer being an absorbable medical film and the other surface layer being a substrate; the preparation material of the absorbable medical film is selected from L-polylactic acid-polycaprolactone copolymer.

[0008] In some specific embodiments, the preparation material of the absorbable medical membrane is L-polylactic acid-polycaprolactone copolymer, the polymerization ratio of L-lactide to ε-caprolactone of the L-polylactic acid-polycaprolactone copolymer is 50-75:25-50, and the intrinsic viscosity is 0.5-1.5 dl / g; the substrate is a non-absorbable material, and the substrate is polypropylene.

[0009] In some specific embodiments, the absorbable medical film has a thickness of 0.04 mm to 0.2 mm, and the substrate has a thickness of 0.32 mm to 0.55 mm.

[0010] In some specific embodiments, the surface of the absorbable medical membrane has uniformly dense drainage holes with a pore size of 0.1 mm to 2 mm and a pore spacing of 0.5 cm to 3.5 cm.

[0011] In some specific embodiments, the absorbable medical membrane is made by a casting method or an electrostatic spinning method, and the absorbable medical membrane is combined with the substrate by heat pressing, bonding or suturing.

[0012] In some specific embodiments, the absorbable medical film is a dyed marking film to distinguish the front and back sides of the patch.

[0013] The base material of the anti-adhesion hernia repair patch is a mesh woven fabric with a double-comb three-needle warp satin mesh structure. Two combs are moved horizontally to the left and right to symmetrically pad the yarn into circles to form a diamond mesh structure. Both combs are one through and one empty.

[0014] In some specific embodiments, the substrate is woven from white medical polypropylene monofilaments with a diameter of 0.1 mm to 0.2 mm and blue medical polypropylene monofilaments with a diameter of 0.10 to 0.20 mm.

[0015] In some specific embodiments, the usage ratio of the white medical polypropylene monofilament to the blue medical polypropylene monofilament is 6:1.

[0016] In some specific embodiments, the pore size of the diamond mesh structure is 1 mm to 5 mm.

[0017] In some specific embodiments, the weight per unit area of ​​the substrate is 30 g / m 2 ~60g / m 2 .

[0018] In some embodiments, the substrate has a machine direction pulling density of 8 rows / cm.

[0019] In some specific embodiments, the inlay yarn numbers of the substrate are GB1 10 / 12 / 23 / 21 / / one through and one empty, GB222 / 21 / 10 / 12 / / one through and one empty.

[0020] The utility model also provides a base material for an anti-adhesion hernia repair patch, which is a mesh woven fabric with a double-comb three-needle warp satin mesh structure. Two combs are moved horizontally left and right to symmetrically pad yarns into loops to form a diamond mesh structure. Both combs are one through and one empty.

[0021] Compared with the prior art, the utility model has the following beneficial effects:

[0022] The utility model has good tensile strength, good abdominal wall compliance, small foreign body reaction, can promote tissue growth, and can effectively prevent adhesion. The side of the anti-adhesion hernia repair patch close to the abdominal wall uses a non-absorbable woven material as a base material. The unique woven structure has the advantages of moderate pore size, light weight per unit area, and good mechanical properties, which can reduce the risk of patch rupture due to insufficient mechanical properties of the patch after surgery.

[0023] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the weaving structure. DETAILED DESCRIPTION

[0025] In order to make the technical means, creative features, objectives and effects of the utility model easier to understand, the utility model is further described below with reference to specific diagrams. However, the utility model is not limited to the following implementation cases.

[0026] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings in this specification are only used to match the contents disclosed in the specification so that people familiar with this technology can understand and read them. They are not used to limit the conditions under which the present utility model can be implemented, so they have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical contents disclosed in the present utility model without affecting the effects and purposes that can be achieved by the present utility model.

[0027] Test items and test methods

[0028] 1. Thickness

[0029] The fabric thickness tester is used for testing, and the circular presser foot area is 2000±20mm 2 , pressurizing pressure 1±0.01KPa (200cN), pressurizing time 10±2s.

[0030] 2. Weight per unit area

[0031] Use a cutter at an appropriate location to cut the sample into a 10 cm x 10 cm square or an area of ​​100 cm 2 The circular sample is weighed with a balance to an accuracy of 0.01g. The unit area weight of the sample is: M = 100m

[0032] M is the weight of the sample per unit area, in grams per square meter (g / m2); m is the weight of the sample weighed, in grams (g).

[0033] 3. Aperture

[0034] The main pores on the patch surface are rhombus-shaped, so the pore size of the main pores of the patch is expressed as: L×S (unit: mm), where L and S refer to the longest and shortest distances between the corresponding fiber nodes that make up each pore, respectively.

[0035] The samples are photographed by scanning electron microscopy or optical microscopy, and the L value and S value of each morphology of the main pores in each microscopic image are measured respectively.

[0036] 4. Bursting strength

[0037] Cut 100cm with a cutter 2 The disc is tested using an electronic fabric strength tester. Replace the special fixture for bursting strength test, adjust the limit line to the lower line, open the tensile testing machine software, select bursting in the settings, and set the parameters: clamping distance 100mm; pretension 0.2N; moving speed 300mm / min; fixed point force 800N; fixed point elongation 250%.

[0038] 5. Tensile strength

[0039] Cut the sample into 25×150mm longitudinal and transverse strips and use an electronic fabric strength tester to test it. Replace the upper and lower clamps with 25×100mm, adjust the limit line to the upper line, open the software, select stretching in the settings, and set the parameters: clamping distance 100mm; pretension 2N; moving speed 100mm / min; fixed point force 500N; fixed point elongation 500%.

[0040] 6. Tear strength

[0041] According to the method specified in GB / T3917.3-2009, the samples were cut into 75×150mm longitudinal and transverse trapezoidal samples and tested using an electronic fabric strength tester. Replace the upper and lower clamps with 25×100mm, adjust the limit line to the upper line, open the software, select tear strength in the settings, and set the parameters: clamping distance 25mm; pretension 0.2N; moving speed 100mm / min; fixed point force 800N; fixed point elongation 500%.

[0042] 7. Suture strength

[0043] Cut the sample into 50×50mm and test it with an electronic fabric strength tester. Replace the upper and lower clamps with 25×100mm, adjust the limit line to the upper line, open the software, select peeling in the settings, and set the parameters: clamping distance 100mm; pretension 0.2N; moving speed 100mm / min; fixed point force 800N; fixed point elongation 500%. Fix the sample on the clamp, use a suture with sufficient strength (suture specification: 0) to pass through the patch at one end of the patch (6-12mm from the edge), sew it into a semi-ring, and the suture is stretched at a speed of 100mm / min. Record the pulling force that pulls the suture out of the patch or damages the patch.

[0044] Example

[0045] An anti-adhesion hernia repair patch is a two-layer structure, with an absorbable medical membrane arranged on a specially designed warp knitted structure substrate. The absorbable medical membrane is made of L-polylactic acid-polycaprolactone copolymer, with a polymerization ratio of L-lactide to ε-caprolactone of 50:50 and a thickness of 0.08 mm. The L-polylactic acid-polycaprolactone copolymer was purchased from Jinan Jufukai Biotechnology Co., Ltd. The surface of the absorbable medical membrane has uniformly dense drainage holes with a pore diameter of 0.1 mm and a pore spacing of 1.0 cm. The monofilament of the warp knitted structure substrate uses white and blue medical polypropylene monofilaments with a diameter of 0.15 mm, and the ratio of white and blue medical polypropylene monofilaments is 6:1. On a warp knitting machine with a machine number of E18, two combs are used, one of the front combs is through and the other is empty, and the other of the rear combs is through and the other is empty. A double-comb three-needle warp satin mesh structure is adopted. The two combs are moved horizontally to the left and right to form a symmetrical yarn loop in opposite directions, forming a diamond mesh structure. Figure 1 As shown, the yarn numbers of the two comb bars, the front comb bar GB1 and the back comb bar GB2, are as follows: GB1 10 / 12 / 23 / 21 / / one through and one empty, GB2 22 / 21 / 10 / 12 / / one through and one empty. The longitudinal pulling density is 8 rows / cm.

[0046] The mesh fabric woven by this method has a thickness of 0.45 mm and a weight per unit area of ​​48 g / m 2, pore size is 2mm~4mm, longitudinal pore size is 3mm~4mm, transverse pore size is 2mm~3mm; bursting strength ≥477N; transverse tensile strength ≥57N, longitudinal tensile strength ≥143N; transverse tear strength ≥84N, longitudinal tear strength ≥81N, transverse suture strength ≥37N, longitudinal suture strength ≥35N. The detailed test results are shown in Table 1 below:

[0047] Table 1 Fabric test results

[0048]

[0049] Comparative Example

[0050] Patent CN105266923A discloses a lightweight hernia repair patch and its weaving method, which is characterized in that: the variable chain warp satin structure refers to a structure formed by adding chain yarns equally between two adjacent turning coils in each yarn padding direction in a complete structure of three-needle warp satin, wherein the number of horizontal rows of chain yarns added between two adjacent turning coils in the same yarn padding direction is 1 to 4, and the opening and closing forms of the coils in the organization can be arbitrarily changed and configured. The transverse density of the hernia repair patch is: 15 to 40 longitudinal rows / 5cm, and the longitudinal density is: 35 to 125 horizontal rows / 5cm. On the warp knitting machine, a comb is installed, and the medical synthetic monofilament is unwound from the warp shaft and enters the loop forming system according to a certain warp feed amount. According to the variable chain warp satin structure yarn padding number, the yarn guide needle makes regular yarn padding movement to form a mesh braided fabric. A lightweight hernia repair patch woven by this method is compared with the physical properties of the fabric woven by this weaving method. The comparison data is shown in Table 3:

[0051] Table 3 Comparison results of test data

[0052]

[0053] The maximum rupture strength that the human transverse abdominal fascia can withstand is 232N, and the maximum tension of the human abdominal wall is 16N / cm. It can be seen from the above 7 data that the specially designed warp knitted structure base fabric of this embodiment and the patented CN105266923A fabric are fully capable of withstanding the mechanical strength required by human physiology, and the test data of this embodiment is significantly better than that of the patented CN105266923A fabric.

[0054] The preferred specific embodiments of the utility model are described in detail above. It should be understood that ordinary technology in the field can make many modifications and changes according to the concept of the utility model without creative work. Therefore, any technical solution that can be obtained by a technician in the technical field based on the concept of the utility model through logical analysis, reasoning or limited experiments on the basis of the existing technology should be within the scope of protection determined by the claims.

Claims

1. An anti-adhesion hernia repair patch, characterized in that: It is a two-layer or multi-layer structure, one surface layer is an absorbable medical film; it also includes a base material; the thickness of the absorbable medical film is 0.04mm-0.2mm, the thickness of the base material is 0.32mm-0.55mm; the base material is a mesh woven fabric.

2. The anti-adhesion hernia repair patch according to claim 1, characterized in that: The surface of the absorbable medical membrane is provided with evenly distributed drainage holes, the hole diameter is 0.1mm-2mm, and the hole distance is 0.5cm-3.5cm.

3. The anti-adhesion hernia repair patch according to claim 1, characterized in that: The absorbable medical film is combined with the substrate by heat pressing, bonding or sewing.

4. The anti-adhesion hernia repair patch according to claim 1, characterized in that: The base material has a double-comb three-needle warp satin mesh structure, and two combs are moved horizontally to the left and right to symmetrically pad yarns into loops in opposite directions to form a diamond mesh structure, and both combs are one through and one empty.

5. The anti-adhesion hernia repair patch according to claim 4, characterized in that: The base material is woven from white medical polypropylene monofilaments with a diameter of 0.1mm-0.2mm and blue medical polypropylene monofilaments with a diameter of 0.10-0.20mm; the padding yarn numbers of the base material are GB1 10 / 12 / 23 / 21 / / one through and one empty, GB2 22 / 21 / 10 / 12 / / one through and one empty.

6. The anti-adhesion hernia repair patch according to claim 5, characterized in that: The aperture of the diamond mesh structure is 1 mm to 5 mm, and the longitudinal pulling density of the substrate is 8 horizontal rows / cm.

Citation Information

Patent Citations

  • Light hernia repair patch and knitting method

    CN105266923A